Entropic patchiness: Effects of colloid shape and depletion. (July 2017) - Petukhov, Andrei V.; Tuinier, Remco; Vroege, Gert Jan
Abstract: This paper reviews 'entropic patchiness' of colloidal particles. On the one hand this may be due to their intrinsic tendency to form certain shape-dependent configurations in crowded suspensions, on the other hand this can be strongly enhanced by using depletion interactions that are also of purely entropic origin. A brief account of the Onsager theory and its consequences for the formation of colloidal liquid crystals of highly anisometric particles is presented. It is further supplemented by a recap of the description of depletion attraction between colloids and the effects of their shape. A number of recent examples exploiting entropic patchiness are discussed. Graphical abstract: Highlights: Non-spherical hard colloidal particles can exhibit directionality purely based on entropic interactions. Interplay between orientational and excluded volume entropy enables to induce multiple liquid-crystalline phases. Depletion interactions can strongly enhance entropic patchiness of hard colloids. Variation of particle shape, strength and range of depletion attraction yields a wide variety of self-assembled structures.